Budget Limitations and Policy Implementation Outcomes in Community Empowerment Programs - Bakri La Suhu; Darwin Abd Radjak; Rasid Pora (Universitas Tribhuwana Tungga Dewi, 2026)
This study aims to analyze the implementation of community empowerment policies in Kalumpang Village, Ternate City, with a focus on identifying key factors affecting policy effectiveness. The study addresses the problem of suboptimal program outcomes despite the existence of a formal regulatory framework. A qualitative research approach is employed, using a policy implementation framework that emphasizes four key variables: communication, resources, implementer disposition, and bureaucratic structure. The findings indicate that although internal communication and implementer commitment are relatively strong, program effectiveness remains limited. Budget constraints are identified as the most dominant factor affecting program coverage and sustainability, while top-down communication patterns restrict community participation. These results demonstrate that policy implementation is a multidimensional process shaped by the interaction of various factors. This study contributes to the literature by providing empirical evidence on the importance of an integrated and context-sensitive approach to improving community empowerment policies in decentralized governance settings.